2010
DOI: 10.3944/aott.2010.2289
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the results of open and arthroscopic repair of isolated traumatic anterior instability of the shoulder

Abstract: Although, in the past, the results of arthroscopic repair were less satisfactory compared to open surgery, this condition has changed remarkably. The results of arthroscopic repair in our study were similar to those of open repair. We believe that, with enhanced experience and advances in arthroscopic repair techniques, arthroscopic treatment may outweigh open surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…Three percent of cases (20 of 636) from 14 studies 1,5,6,9,13,[15][16][17]19,22,24,32,41,45 were revision procedures. Sixteen studies 4,12,29,31,33,36,39,[43][44][45]47,[49][50][51][52][53] (1058 cases) made no comment regarding whether the procedures were primary or revision cases. Metallic screw fixation was used in 29 studies, 1,[4][5][6]9,12,13,[15][16][17]19,22,24,29,[31][32][33]36,[42][43][44]…”
Section: Resultsmentioning
confidence: 99%
“…Three percent of cases (20 of 636) from 14 studies 1,5,6,9,13,[15][16][17]19,22,24,32,41,45 were revision procedures. Sixteen studies 4,12,29,31,33,36,39,[43][44][45]47,[49][50][51][52][53] (1058 cases) made no comment regarding whether the procedures were primary or revision cases. Metallic screw fixation was used in 29 studies, 1,[4][5][6]9,12,13,[15][16][17]19,22,24,29,[31][32][33]36,[42][43][44]…”
Section: Resultsmentioning
confidence: 99%
“…While a large number of studies have looked at recurrence of shoulder instability following arthroscopic Bankart repair, a large degree of variability exists ranging from 3.4 to 33.3% lifetime recurrence rate, with an average rate of 13.1% when pooling 12 high-quality trials [8,[57][58][59][60][61][62][63][64]. The reported recurrence rate after arthroscopic Bankart repair ranges from 4 to 19% [65]; in newer literature, the risk is increased by participation in contact sports [66].…”
Section: Recurrence Of Shoulder Instabilitymentioning
confidence: 99%
“…Following arthroscopic Bankart repair, average external rotation is commonly decreased, both with the arm at the side (ranging between 3.5 and 9°) and with the arm abducted to 90°( ranging between 3.5 and 7°) [8,[57][58][59]68]. Similarly, a small degree of average loss of forward flexion is to be expected, ranging 1-3° [57].…”
Section: Range Of Motion (Rom)mentioning
confidence: 99%
“…In our denced movement restriction in both surgical repairs, Latarjet and Bankart, the latter implying about 6˚ of significant postoperative restriction [56]. Regarding open surgery, one of the explanations for reduction or loss of external and internal rotation includes excessive capsule thickening, cut or shortening of subscapularis tendon, and especially, the development of fibrosis in the reconstructed capsulolabral complex [38]. In our review, we identified 11 patients with external rotation limitation and 7 patients with motion restriction.…”
Section: Repair Failurementioning
confidence: 99%
“…In our review, we identified 11 patients with external rotation limitation and 7 patients with motion restriction. The limitations of this systematic review are directly related to the quality of selected studies and their inherent biases, as well as the absence by some studies of the citation of their level of evidence [38] …”
Section: Repair Failurementioning
confidence: 99%